Hydrogen bonding in the ethanol–water dimer. Issue 37 (1st September 2015) - Finneran, Ian A.; Carroll, P. Brandon; Allodi, Marco A.; Blake, Geoffrey A.
Abstract : We report the first rotational spectrum of the ground state of the isolated ethanol–water dimer using chirped-pulse Fourier transform microwave spectroscopy between 8–18 GHz. Abstract : We report the first rotational spectrum of the ground state of the isolated ethanol–water dimer using chirped-pulse Fourier transform microwave spectroscopy between 8–18 GHz. With the aid of isotopic substitutions, and ab initio calculations, we identify the measured conformer as a water-donor/ethanol-acceptor structure. Ethanol is found to be in the gauche conformation, while the monomer distances and orientations likely reflect a cooperation between the strong (O–H⋯O) and weak (C–H⋯O) hydrogen bonds that stabilizes the measured conformer. No other conformers were assigned in an argon expansion, confirming that this is the ground-state structure. This result is consistent with previous vibrationally-resolved Raman and infrared work, but sheds additional light on the structure, due to the specificity of rotational spectroscopy.